2020
DOI: 10.1097/sap.0000000000002343
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes After Hematoma Development

Abstract: Background Hematomas after tissue expander immediate breast reconstruction (TE-IBR) pose a significant challenge during the recovery period. In this study, we aim to evaluate whether hematoma formation leads to subsequent complications and how management can impact final reconstructive goals. Methods A single-institution retrospective review of TE-IBRs from 2001 to 2018 was performed using an established breast reconstruction database. Demographics, med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The incidence of hematomas after alloplastic breast reconstruction has been reported to range from 1% to 5% 15,16 . For TE-IBR patients who develop postoperative hematomas, the outcomes after the complication can be potentially devastating, as hematomas significantly increase the risk of other complications such as capsular contracture, infections, implant loss, and reconstructive failure 16–18 . Therefore, surgeons may be hesitant to discharge their patients home the day of surgery because of the risk of forming a hematoma in the immediate postoperative period and delaying treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of hematomas after alloplastic breast reconstruction has been reported to range from 1% to 5% 15,16 . For TE-IBR patients who develop postoperative hematomas, the outcomes after the complication can be potentially devastating, as hematomas significantly increase the risk of other complications such as capsular contracture, infections, implant loss, and reconstructive failure 16–18 . Therefore, surgeons may be hesitant to discharge their patients home the day of surgery because of the risk of forming a hematoma in the immediate postoperative period and delaying treatment.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 For TE-IBR patients who develop postoperative hematomas, the outcomes after the complication can be potentially devastating, as hematomas significantly increase the risk of other complications such as capsular contracture, infections, implant loss, and reconstructive failure. [16][17][18] Therefore, surgeons may be hesitant to discharge their patients home the day of surgery because of the risk of forming a hematoma in the immediate postoperative period and delaying treatment. A recent systematic review with a total of 285 same-day discharge patients found that ERAS protocols after immediate alloplastic breast reconstruction had no difference in overall complication rates, including hematomas, between same-day discharge and overnight admission patients.…”
Section: Discussionmentioning
confidence: 99%